Policy construction of the Constitution of the Republic Indonesia political system rergarding the implementation of the president's prerogative in the appointment of ministers in the era of Joko Widodo administration - Hendrawati, Sulkiah; Santiago, Faisal; Fakrulloh, Zudan Arif (International Journal Labs, 2024)
The prerogative of the President in appointing a minister is defined by the 1945 Constitution. The research uses an empirical legal approach method to analyze the practical implications and real-world applications of constitutional provisions, examining the political and legal impacts of these appointments, and exploring the broader socio-political context of such decisions within the framework of Indonesia's evolving political landscape under President Joko Widodo's administration. This paper focuses on the theoretical and practical implications of the 1945 constitution and the concept of a legal state as the law that serves as the foundation of governance and must be complied with in exercising power, bridges the gap between despotic absolutism and the advanced development of constitutionalism, thus leading to the formation of constitutional law.